Electromagnetic stealth coating and preparation method thereof

By coating carbon quantum dot solution on the nickel-based alloy matrix layer to form an electromagnetic invisible coating, the complex and cost-effective preparation problems in the prior art are solved, and the efficient electromagnetic invisible effect is achieved, with reflection loss reaching -80dB and effective absorption The bandwidth reaches 10GHz.

CN118374800BActive Publication Date: 2024-12-17NANJING UNIV OF POSTS & TELECOMM
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202410465185.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-18
Publication Date
2024-12-17
Estimated Expiration
2044-04-18

AI Technical Summary

Technical Problem

The existing electromagnetic invisible coating preparation methods are complex, costly, unsatisfactory shielding effect, maximum reflection loss is -40dB, and limited effective absorption bandwidth, resulting in poor electromagnetic invisible effect.

Method used

Carbon quantum dot solution is applied on the nickel-based alloy matrix layer by water bath method, and carbon quantum dots are grown and deposited in situ to form an electromagnetic stealth coating, simplifying the preparation process, reducing costs, and improving wave absorption performance.

Benefits of technology

It achieves reflection loss up to -80dB, effective absorption bandwidth up to 10GHz, and has broadband electromagnetic stealth function, simple operation and low cost, and is suitable for dual-use and electromagnetic pollution treatment of military and civilians.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118374800B_ABST
    Figure CN118374800B_ABST
Patent Text Reader

Abstract

The invention discloses an electromagnetic stealth coating and a preparation method thereof, belonging to the technical field of electromagnetic stealth coatings, comprising: preparing a carbon quantum dot solution; coating the carbon quantum dot solution on a nickel-based alloy substrate layer by a water bath method; in-situ growth and deposition of carbon quantum dots on the nickel-based alloy substrate layer to obtain an electromagnetic stealth coating; the preparation method of the invention has the characteristics of simple operation method, extremely low cost and mass production, and has broad application prospects in military and civilian dual-use stealth coatings and electromagnetic pollution treatment; has excellent wave absorbing performance, and can achieve a maximum reflection loss of 80dB, thereby achieving an excellent electromagnetic stealth effect; the effective absorption bandwidth (reflection loss < 10dB, that is, the range of shielding more than 90% of incident electromagnetic waves) reaches 10 GHz, thereby achieving a broadband electromagnetic stealth function.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electromagnetic stealth coating and a preparation method thereof, belonging to the technical field of electromagnetic stealth coatings. Background Art

[0002] The rapid development of radar technology poses a serious threat to the survival of modern weapons and equipment. In order to improve the survivability of weapons and equipment in modern and future wars, it is particularly important to develop absorbing coatings to reduce the radar reflection area of ​​equipment systems. At present, electromagnetic stealth coatings are mostly polymers, SiC, Ti3SiC2, magnetic metal powders and MXene materials. For example, the Chinese invention patent application with application number CN202011282511.9 and publication number CN112391833A discloses a lightweight and efficient absorbing material SnFe2O4 / C composite nanofiber absorbing coating. For example, the Chinese invention patent with application number CN202211096504.9 and publication number CN115595026A discloses a method for preparing a MXene-based absorbing coating, and a mixed coating slurry whose main components are MXene powder and iron salt solution is prepared by heating, filtering, mixing, drying and plasma spraying. Similar to the above-mentioned stealth absorbing coatings, most stealth coating materials have the disadvantages of complex preparation methods, a variety of manufacturing materials, or the need to pre-treat the metal substrate, which leads to high manufacturing costs and complicated manufacturing conditions for electromagnetic stealth coatings. In addition, the existing stealth coatings have a maximum reflection loss of around -40dB, and most of the effective absorption bandwidth is between 2.0GHz and 3.5GHz, and the shielding effect is generally not ideal. Summary of the invention

[0003] The purpose of the present invention is to provide an electromagnetic stealth coating and a preparation method thereof, so as to solve the problems of high preparation cost and poor shielding effect existing in the prior art.

[0004] To achieve the above objectives, the present invention is implemented by adopting the following technical solutions:

[0005] In a first aspect, the present invention provides a method for preparing an electromagnetic stealth coating, comprising:

[0006] preparing a carbon quantum dot solution;

[0007] coating the carbon quantum dot solution on the prepared nickel-based alloy substrate layer by a water bath method;

[0008] Carbon quantum dots are in-situ grown and deposited on a nickel-based alloy substrate layer to obtain an electromagnetic stealth coating.

[0009] Furthermore, the preparation of the carbon quantum dot solution comprises:

[0010] Anhydrous glucose and sodium hydroxide are dissolved in deionized water to make the molar concentrations of anhydrous glucose and sodium hydroxide 0.45-0.55 mol / L, and ultrasonicated at 30-50° C. for 1-5 hours to obtain a yellow-brown carbon quantum dot solution.

[0011] Furthermore, the frequency of the ultrasound is 38-42 KHz.

[0012] Furthermore, the step of coating the carbon quantum dot solution on the prepared nickel-based alloy substrate layer by a water bath method comprises:

[0013] The nickel-based alloy substrate layer is placed in the carbon quantum dot solution and heated in a water bath at a temperature above 40° C. for 2 to 5 hours.

[0014] Furthermore, after the coating is completed, it also includes:

[0015] Wash three times with deionized water and anhydrous ethanol;

[0016] Place in a 50~70℃ oven and dry for 11~13 hours.

[0017] In a second aspect, the present invention provides an electromagnetic stealth coating prepared by the method described in any one of the first aspects, comprising a nickel-based alloy substrate layer and a carbon quantum dot layer, wherein the carbon quantum dot layer is in-situ grown and deposited on the surface of the nickel-based alloy substrate layer.

[0018] Furthermore, the nickel-based alloy matrix layer is doped with copper, chromium, molybdenum and tungsten.

[0019] Furthermore, the thickness of the carbon quantum dot layer is 1-50 nm.

[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0021] The present invention provides an electromagnetic stealth coating and a preparation method thereof. The preparation method has the characteristics of simple operation, extremely low cost and mass production, and has broad application prospects in dual-use stealth coatings for military and civilian use and electromagnetic pollution treatment. The coating has excellent wave absorbing performance, and can achieve a maximum reflection loss of -80dB, thereby achieving a superior electromagnetic stealth effect. The effective absorption bandwidth (reflection coefficient <-10dB, i.e., a range that can shield more than 90% of incident electromagnetic waves) reaches 10 GHz, thereby achieving a broadband electromagnetic stealth function. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a flow chart of a method for preparing an electromagnetic stealth coating provided by an embodiment of the present invention;

[0023] Figure 2 is a schematic diagram of growing a carbon quantum dot layer by a water bath method provided in an embodiment of the present invention;

[0024] Figure 3 is a schematic diagram of an electromagnetic stealth coating provided by an embodiment of the present invention;

[0025] Figure 4 It is a schematic diagram of the reflection loss of the electromagnetic stealth coating prepared in Example 5 of the present invention.

[0026] In the figure: 1. Beaker; 2. Carbon quantum dot solution; 3. Electromagnetic stealth coating; 4. Carbon quantum dot layer; 5. Nickel-based alloy substrate layer. DETAILED DESCRIPTION

[0027] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solutions of the present invention and are not intended to limit the protection scope of the present invention.

[0028] Example 1, using Figure 1 The method shown in the figure is to prepare an electromagnetic stealth coating, which specifically includes the following steps:

[0029] 1) A carbon quantum dot solution was prepared using anhydrous glucose and sodium hydroxide as raw materials. The specific method was as follows: a certain amount of anhydrous glucose and sodium hydroxide were dissolved in deionized water so that the molar concentration of both was 0.5 mol / L, and the solution was ultrasonicated at 40°C for 3 hours to obtain a yellow-brown carbon quantum dot solution according to the ultrasonic time.

[0030] 2) The carbon quantum dot coating is applied by water bath method, such as Figure 2 As shown, the specific steps are:

[0031] A square metal nickel plate with a thickness of 0.5 mm and a size of 180 mm × 180 mm was placed in a carbon quantum dot solution, heated in a water bath at 60°C for 2 hours, taken out and washed three times with deionized water and anhydrous ethanol respectively, and placed in a 60°C oven to dry for 12 hours to obtain an electromagnetic stealth coating covered with carbon material.

[0032] The electromagnetic stealth coating in this embodiment is formed by heating and immersing a nickel-based alloy in a carbon quantum dot solution, and the carbon quantum dots grow spontaneously on the surface of the nickel-based alloy to form a coating.

[0033] Figure 2 In the figure, 1 is a beaker, 2 is a carbon quantum dot solution, and 3 is an electromagnetic stealth coating.

[0034] The nickel-based alloy is a metal nickel film, a metal nickel plate, or a nickel-based alloy film or a nickel-based alloy plate doped with elements such as copper, chromium, molybdenum, and tungsten.

[0035] The dielectric constant and magnetic permeability of the 180mm×180mm×0.5mm nickel plate coated with carbon coating (ultrasound for 3 hours) were measured by vector network analyzer, and the reflection loss and effective absorption bandwidth (reflection coefficient <-10dB) of the electromagnetic stealth coating were calculated according to the reflection loss formula. The thickness of the electromagnetic stealth coating was measured by ellipsometry.

[0036] The experimental results show that the electromagnetic stealth coating based on the metal nickel plate with a size of 180mm×180mm×0.5mm (ultrasound for 3 hours) has a maximum reflection coefficient of -80 dB, an effective absorption bandwidth (reflection coefficient <-10dB) of 3.9GHz, and a coating thickness of 25.5nm.

[0037] The test conditions of this embodiment are as follows:

[0038] Vector network analyzer, instrument model: Agilent E5071c, USA; test method: bow method; sample size: 180mm×180mm; frequency range: 1-18GHz.

[0039] Ellipsometer, instrument model: Semilab SE-2000; test method: optical reflection mode; spectral range: UV-visible-near infrared (245 nm~1700 nm).

[0040] Example 2, using Figure 1 The method shown in the figure is to prepare an electromagnetic stealth coating, which specifically includes the following steps:

[0041] 1) A carbon quantum dot solution was prepared using anhydrous glucose and sodium hydroxide as raw materials. The specific method was as follows: a certain amount of anhydrous glucose and sodium hydroxide were dissolved in deionized water so that the molar concentration of both was 0.5 mol / L, and the solution was ultrasonicated at 40°C for 4 hours to obtain a yellow-brown carbon quantum dot solution according to the ultrasonic time.

[0042] 2) The carbon quantum dot coating is applied by water bath method, such as Figure 2 As shown, the specific steps are:

[0043] A circular nickel-based alloy (nickel-copper alloy Ni70-Cu30) with a thickness of 0.5 mm and a size of 100 mm×100 mm was placed in a carbon quantum dot solution, heated in a water bath at 60°C for 2 hours, taken out and washed three times with deionized water and anhydrous ethanol, and placed in a 60°C oven for 12 hours to obtain an electromagnetic stealth coating covered with carbon material. The dielectric constant and magnetic permeability of the nickel-based alloy (nickel-copper alloy Ni70-Cu30) coated with a carbon coating (ultrasound for 4 hours) were measured using a vector network analyzer, and the reflection loss and effective absorption bandwidth (reflection coefficient <-10dB) of the electromagnetic stealth coating were calculated according to the reflection loss formula. The thickness of the electromagnetic stealth coating was measured using an ellipsometer.

[0044] The experimental results show that the electromagnetic stealth coating (ultrasound for 4 hours) based on a circular nickel-based alloy (nickel-copper alloy Ni70-Cu30) with a size of 100mm×100mm×0.5mm has a maximum reflection coefficient of -43.7 dB, an effective absorption bandwidth (reflection coefficient <-10dB) of 4.2GHz, and a coating thickness of 38.2nm.

[0045] The test conditions of this embodiment are as follows:

[0046] Vector network analyzer, instrument model: Agilent E5071c, USA; test method: bow method; sample size: 100mm×100mm; frequency range: 1-18GHz.

[0047] Ellipsometer, instrument model: Semilab SE-2000; test method: optical reflection mode; spectral range: UV-visible-near infrared (245 nm~1700 nm).

[0048] Example 3, using Figure 1 The method shown in the figure is to prepare an electromagnetic stealth coating, which specifically includes the following steps:

[0049] 1) A carbon quantum dot solution was prepared using anhydrous glucose and sodium hydroxide as raw materials. The specific method was as follows: a certain amount of anhydrous glucose and sodium hydroxide were dissolved in deionized water so that the molar concentration of both was 0.5 mol / L, and the solution was ultrasonicated at 40°C for 3 hours to obtain a yellow-brown carbon quantum dot solution according to the ultrasonic time.

[0050] 2) The carbon quantum dot coating is applied by water bath method, such as Figure 2 As shown, the specific steps are:

[0051] A square nickel-based alloy (nickel-chromium alloy Ni80-Cr20) with a thickness of 0.1 mm and a size of 100 mm×100 mm was placed in a carbon quantum dot solution, heated in a water bath at 60°C for 2 hours, taken out and washed three times with deionized water and anhydrous ethanol each, and placed in an oven at 60°C to dry for 12 hours to obtain an electromagnetic stealth coating covered with carbon material.

[0052] The dielectric constant and magnetic permeability of 100mm×100mm×0.1mm nickel-based alloy (nickel-chromium alloy Ni80-Cr20) coated with carbon coating (ultrasound for 3 hours) were measured by vector network analyzer, and the reflection loss and effective absorption bandwidth (reflection coefficient <-10dB) of the electromagnetic stealth coating were calculated according to the reflection loss formula. The thickness of the electromagnetic stealth coating was measured by ellipsometry spectrometer.

[0053] The experimental results show that the electromagnetic stealth coating (ultrasound for 3 hours) based on nickel-based alloy (nickel-chromium alloy Ni80-Cr20) with a size of 100mm×100mm×0.1mm has a maximum reflection coefficient of -48.7 dB, an effective absorption bandwidth (reflection coefficient <-10dB) of 4.5GHz, and a coating thickness of 27.1nm.

[0054] The test conditions of this embodiment are as follows:

[0055] Vector network analyzer, instrument model: Agilent E5071c, USA; test method: bow method; sample size: 100mm×100mm; frequency range: 1-18GHz.

[0056] Ellipsometer, instrument model: Semilab SE-2000; test method: optical reflection mode; spectral range: UV-visible-near infrared (245 nm~1700 nm).

[0057] Example 4, using Figure 1 The method shown in the figure is to prepare the electromagnetic stealth coating, such as Figure 2 As shown, the specific steps include:

[0058] 1) A carbon quantum dot solution was prepared using anhydrous glucose and sodium hydroxide as raw materials. The specific method was as follows: a certain amount of anhydrous glucose and sodium hydroxide were dissolved in deionized water so that the molar concentration of both was 0.5 mol / L, and the solution was ultrasonicated at 40°C for 5 hours to obtain a yellow-brown carbon quantum dot solution according to the ultrasonic time.

[0059] 2) The carbon quantum dot coating is applied by a water bath method. The specific steps are as follows:

[0060] A square nickel-based alloy (nickel-molybdenum alloy Ni70-Mo30) with a thickness of 0.5 mm and a size of 180 mm × 180 mm was placed in a carbon quantum dot solution, heated in a water bath at 60°C for 2 hours, taken out and washed three times with deionized water and anhydrous ethanol each, and placed in an oven at 60°C to dry for 12 hours to obtain an electromagnetic stealth coating covered with carbon material.

[0061] The dielectric constant and magnetic permeability of a 180mm×180mm×0.5mm nickel-based alloy (nickel-molybdenum alloy Ni70-Mo30) coated with a carbon coating (ultrasound for 5 hours) were measured using a vector network analyzer, and the reflection loss and effective absorption bandwidth (reflection coefficient <-10dB) of the electromagnetic stealth coating were calculated according to the reflection loss formula. The thickness of the electromagnetic stealth coating was measured using an ellipsometry spectrometer.

[0062] The test results show that the electromagnetic stealth coating (ultrasound for 5 hours) based on nickel-based alloy (nickel-molybdenum alloy Ni70-Mo30) with a size of 180mm×180mm×0.5mm has a maximum reflection coefficient of -68.7 dB, an effective absorption bandwidth (reflection coefficient <-10dB) of 8.5GHz, and a coating thickness of 44.1nm.

[0063] The test conditions of this embodiment are as follows:

[0064] Vector network analyzer, instrument model: Agilent E5071c, USA; test method: bow method; sample size: 180mm×180mm; frequency range: 1-18GHz.

[0065] Ellipsometer, instrument model: Semilab SE-2000; test method: optical reflection mode; spectral range: UV-visible-near infrared (245 nm~1700 nm).

[0066] Example 5, using Figure 1 The method shown in the figure is to prepare the electromagnetic stealth coating, such as Figure 2 As shown, the specific steps include:

[0067] 1) A carbon quantum dot solution was prepared using anhydrous glucose and sodium hydroxide as raw materials. The specific method was as follows: a certain amount of anhydrous glucose and sodium hydroxide were dissolved in deionized water so that the molar concentration of both was 0.5 mol / L, and the solution was ultrasonicated at 40°C for 3 hours to obtain a yellow-brown carbon quantum dot solution according to the ultrasonic time.

[0068] 2) The carbon quantum dot coating is applied by water bath method, such as Figure 2 As shown, the specific steps are:

[0069] A square nickel-based alloy (nickel-chromium-molybdenum alloy Ni66-Cr20-Mo14) with a thickness of 0.5 mm and a size of 180 mm×180 mm was placed in a carbon quantum dot solution, heated in a water bath at 60°C for 2 hours, taken out and washed three times with deionized water and anhydrous ethanol each, and placed in an oven at 60°C to dry for 12 hours to obtain an electromagnetic stealth coating covered with carbon material.

[0070] The structure of the electromagnetic stealth coating is as follows: Figure 3 As shown, 4 is a carbon quantum dot layer and 5 is a nickel-based alloy substrate layer.

[0071] The dielectric constant and magnetic permeability of a 180mm×180mm×0.5mm nickel-based alloy (nickel-chromium-molybdenum alloy Ni66-Cr20-Mo14) coated with a carbon coating (ultrasound for 2 hours) were measured using a vector network analyzer, and the reflection loss and effective absorption bandwidth (reflection coefficient <-10dB) of the electromagnetic stealth coating were calculated according to the reflection loss formula. The thickness of the electromagnetic stealth coating was measured using an ellipsometry spectrometer.

[0072] like Figure 4 As shown, the test results show that the electromagnetic stealth coating (ultrasound for 2 hours) based on nickel-based alloy (nickel-chromium-molybdenum alloy Ni66-Cr20-Mo14) with a size of 180mm×180mm×0.5mm has a maximum reflection coefficient of -80.0 dB, an effective absorption bandwidth (reflection coefficient <-10dB) of 10GHz, and a coating thickness of 15.0nm.

[0073] The test conditions of this embodiment are as follows:

[0074] Vector network analyzer, instrument model: Agilent E5071c, USA; test method: bow method; sample size: 180mm×180mm; frequency range: 1-18GHz.

[0075] Ellipsometer, instrument model: Semilab SE-2000; test method: optical reflection mode; spectral range: UV-visible-near infrared (245 nm~1700 nm).

[0076] Example 6, using Figure 1 The method shown in the figure is to prepare an electromagnetic stealth coating, which specifically includes the following steps:

[0077] 1) A carbon quantum dot solution was prepared using anhydrous glucose and sodium hydroxide as raw materials. The specific method was as follows: a certain amount of anhydrous glucose and sodium hydroxide were dissolved in deionized water so that the molar concentration of both was 0.5 mol / L, and the solution was ultrasonicated at 40°C for 3 hours to obtain a yellow-brown carbon quantum dot solution according to the ultrasonic time.

[0078] 2) The carbon quantum dot coating is applied by water bath method, such as Figure 2 As shown, the specific steps are:

[0079] A square nickel-based alloy (nickel-chromium-titanium-aluminum alloy Ni76.2-Cr20-Ti2.5-Al1.3) with a thickness of 0.5 mm and a size of 180 mm×180 mm was placed in a carbon quantum dot solution, heated in a water bath at 60°C for 2 hours, taken out and washed three times with deionized water and anhydrous ethanol each, and placed in an oven at 60°C to dry for 12 hours to obtain an electromagnetic stealth coating covered with carbon material.

[0080] The dielectric constant and magnetic permeability of a 180mm×180mm×0.5mm nickel-based alloy (Ni76.2-Cr20-Ti2.5-Al1.3) coated with a carbon coating (ultrasound for 3 hours) were measured using a vector network analyzer, and the reflection loss and effective absorption bandwidth (reflection coefficient <-10dB) of the electromagnetic stealth coating were calculated according to the reflection loss formula. The thickness of the electromagnetic stealth coating was measured using an ellipsometry spectrometer.

[0081] The experimental results show that the electromagnetic stealth coating (ultrasound for 3 hours) based on nickel-based alloy (nickel-chromium-titanium-aluminum alloy Ni76.2-Cr20-Ti2.5-Al1.3) with a size of 180mm×180mm×0.5mm has a maximum reflection coefficient of -76 dB, an effective absorption bandwidth (reflection coefficient <-10dB) of 8.9GHz, and a coating thickness of 29.4nm.

[0082] The test conditions of this embodiment are as follows:

[0083] Vector network analyzer, instrument model: Agilent E5071c, USA; test method: bow method; sample size: 180mm×180mm; frequency range: 1-18GHz.

[0084] Ellipsometer, instrument model: Semilab SE-2000; test method: optical reflection mode; spectral range: UV-visible-near infrared (245 nm~1700 nm).

[0085] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing an electromagnetic stealth coating, characterized in that: include: Dissolve anhydrous glucose and sodium hydroxide in deionized water to make the molar concentrations of anhydrous glucose and sodium hydroxide 0.45-0.55 mol / L, and perform ultrasound at 30-50° C. for 1-5 hours to obtain a yellow-brown carbon quantum dot solution; coating the carbon quantum dot solution on the prepared nickel-based alloy substrate layer by a water bath method; Carbon quantum dots are in-situ grown and deposited on a nickel-based alloy substrate layer to obtain an electromagnetic stealth coating.

2. The method for preparing the electromagnetic stealth coating according to claim 1, characterized in that: The frequency of the ultrasound is 38-42 KHz.

3. The method for preparing the electromagnetic stealth coating according to claim 1, characterized in that: The method of coating the carbon quantum dot solution on the prepared nickel-based alloy substrate layer by a water bath method comprises: The nickel-based alloy substrate layer is placed in the carbon quantum dot solution and heated in a water bath at a temperature above 40° C. for 2 to 5 hours.

4. The method for preparing the electromagnetic stealth coating according to claim 1, characterized in that: After the coating is completed, the method further includes: washing three times with deionized water and three times with anhydrous ethanol; after washing, drying the surface of the surface of the surface in an oven at 50 to 70° C. for 11 to 13 hours.

5. An electromagnetic stealth coating prepared by the method according to any one of claims 1 to 4, characterized in that: The invention comprises a nickel-based alloy matrix layer and a carbon quantum dot layer, wherein the carbon quantum dot layer is in-situ grown and deposited on the surface of the nickel-based alloy matrix layer.

6. The electromagnetic stealth coating according to claim 5, characterized in that: The nickel-based alloy matrix layer is doped with copper, chromium, molybdenum and tungsten.

7. The electromagnetic stealth coating according to claim 5, characterized in that: The thickness of the carbon quantum dot layer is 1-50 nm.

Citation Information

Patent Citations

  • Light efficient wave-absorbing material SnFe2O4 / C composite nanofiber, wave-absorbing coating and preparation method

    CN112391833A

  • Preparation method of MXene-based wave-absorbing coating

    CN115595026A

  • Method for synthesizing carbon quantum dots on basis of organic micromolecule microwave solid-phase reaction

    CN104192827A

  • Preparation method of yolk type double-shell-layer hollow composite wave absorption material

    CN108330471A

  • Method for simultaneously preparing carbon quantum dots and carbon nanometer balls, and product thereof

    CN109437155A